The Flight of the Eisenstein : The Heresy Unfolds - Swallow, James (Nottingham Black Flame, 2007)
Having witnessed the events on Istvaan III, Deathguard Captain Garro seizes a ship and heads to Terra to warn the Emperor of Horus' treachery. But the fleeing Eisenstein is damaged by enemy fire, and becomes stranded in the warp. Can Garro and his men survive the depradations of Chaos and get his warning to Terra in time?
Keywords: Warhammer (Imaginary place) -- Fiction -- Imaginary wars and battles -- Fiction